Interpreting serological surveys using mixture models: the seroepidemiology of measles, mumps and rubella in England and Wales at the beginning of the 21st century - VYSE, A. J. (Cambridge University Press, 2006)
A mixture modelling technique is applied to age-specific frequency distributions of quantitative results from serological surveys for measles, mumps and rubella using samples collected across the age range in England and Wales in 2000. In accordance with previous studies the analysis suggests that the antibody response to natural infection is stronger than that produced by vaccination, that vaccine-induced antibody levels wane with time and that levels of vaccine-induced antibody response vary for each virus infection being strongest for rubella and weakest for mumps. The current mumps epidemic in the United Kingdom is focused in cohorts born during 1982–1987 who were too old to have received routine MMR vaccination. In the cohort born in 1981–1985 the model estimates that 7·5% have no evidence of mumps specific IgG and 24·9% have the lowest level of detectable antibody. The similar proportions of mumps antibody in these categories among cohorts with opportunity for 1 or 2 doses of vaccine is a concern, as the degree to which these individuals are protected is unclear. Investigations into the efficacy of two doses of a mumps containing vaccine should be a priority during the current epidemic.